Speech Act Analysis of the Trip advisor Hotels Review: A Pragmatics Study - Putu Sarah Kaori Rahmadewi; Ni Nyoman Tri Sukarsih; Gek Wulan Novi Uttami Uttami (LPPM Universitas Dhyana Pura, 2023)
Speech act as the actions performed in saying something This study aims to identify the level of action of speech acts and felicity condition under pragmatics theoretical framework proposed by Austin theory (1969) and support by Searle (1969) and Yule (1996). The qualitative method was used where the data was taken from the utterance of speech act expression found in the hotel review column on the TripAdvisor website from November 2022 until March 2023 using observation, documentation, and note-taking technique by employing purposive sampling technique. The analysis showed that the utterance in hotel review on TripAdvisor website used all types of speech act were locutionary act, illocutionary act, and, perlocutionary act. There were five types of felicity condition were general condition, content conditions, preparatory conditions, sincerity conditions, and essential conditions.